Respuesta :

Answer:

f(a-3) = 5a-17

g(a-3) = a^2-4a+5

Step-by-step explanation:

you would set x equal to a-3 like you would set x equal to 2 for problem a.

f(a-3) = 5(a-3)-2

g(a-3) = (a-3)^2+2(a-3)+2, then simplify

Answer:

The answer to your question is:

e) 5a - 17

f)  a² - 4a  + 5

Step-by-step explanation:

e) f(x) = 5x - 2

  f(a - 3) = 5(a - 3) - 2

             = 5a - 15 - 2

             = 5a - 17

f) g(x) = x² + 2x + 2

  g(a - 3) = (a - 3)² + 2(a - 3) + 2

               = a² - 6a + 9 + 2a - 6 + 2

              = a² - 4a  + 5